2012
DOI: 10.14746/ssllt.2012.2.1.5
|View full text |Cite
|
Sign up to set email alerts
|

EFL learners’ metaphors and images about foreign language learning

Abstract: In this paper, I will argue that awareness of images and metaphors held by foreign language learners about the nature of the target language and its learning can be of substantial value and provide teaching practitioners with useful insights about how to deal with various language learning problems. To elicit images which learners hold about foreign language learning, a questionnaire was given to 350 learners of English in different places in Iran. The questionnaire asked the respondents to provide images abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(32 reference statements)
0
9
0
3
Order By: Relevance
“…Eğitim alanında metaforla ilgili çok sayıda araştırma olmasına karşın Türkçenin yabancı dil olarak öğretimi konusunda metaforla ilgili olarak yapılan çalışmaların istenilen düzeyde olmadığı görülmektedir. Hâlbuki öğrencilerin düşünme süreçlerinin temel içeriğini keşfetmenin bir yolu, öğrencilerin dil öğrenimi hakkında oluşturduğu imgeleri ve metaforları ortaya çıkarmak ve bunlara bakmaktır (Farjami, 2012). Ayrıca öğrencilerin oluşturacakları metaforların yetiştikleri kültürel ortamla bağlantılı olduğunun unutulmaması (Zhang ve Hu, 2009, s. 80) ve yabancı dil eğitiminde farklı kültürlerden gelen öğrencilerin kendi kültürlerine özgü düşünce ve yaşayış özelliklerinin de tespit edilip eğitimin bu durumlar göz önünde bulundurularak düzenlenmesi son derece önemlidir.…”
Section: Metafor üRetimiunclassified
“…Eğitim alanında metaforla ilgili çok sayıda araştırma olmasına karşın Türkçenin yabancı dil olarak öğretimi konusunda metaforla ilgili olarak yapılan çalışmaların istenilen düzeyde olmadığı görülmektedir. Hâlbuki öğrencilerin düşünme süreçlerinin temel içeriğini keşfetmenin bir yolu, öğrencilerin dil öğrenimi hakkında oluşturduğu imgeleri ve metaforları ortaya çıkarmak ve bunlara bakmaktır (Farjami, 2012). Ayrıca öğrencilerin oluşturacakları metaforların yetiştikleri kültürel ortamla bağlantılı olduğunun unutulmaması (Zhang ve Hu, 2009, s. 80) ve yabancı dil eğitiminde farklı kültürlerden gelen öğrencilerin kendi kültürlerine özgü düşünce ve yaşayış özelliklerinin de tespit edilip eğitimin bu durumlar göz önünde bulundurularak düzenlenmesi son derece önemlidir.…”
Section: Metafor üRetimiunclassified
“…There is currently a growing body of research investigating learners' beliefs in diverse education domains. This trend has also gained momentum in language learning, especially in recent decades [28].…”
Section: Language Learners' Beliefsmentioning
confidence: 99%
“…In the second/foreign language (L2) research field, researchers have primarily concentrated on the learner aspect and generally studied beliefs about the experiences in language learning [19,24,26,[28][29][30][31][32][33][34]. Previous studies have shown that learners' beliefs constantly evolve in accordance with learners' previous experiences in the learning process [29,33,34].…”
Section: Language Learners' Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metaphors, which Aristotle just defined as rhetoric ingredients (Wilkes, 1989), but are used in our daily lives unwittingly and have rooted in our sub-conscious (Lakoff and Johnson 2011) in addition to these features, can be used in many fields from not only medicine and science as the best instrument to identify the problems, but also to law and social sciences (Caserett et al 2010;Doring et al 2011;Gravett 2015). As Farjami (2012) reports, a metaphor helps to highlight certain properties of reality while forcing others into the background and therefore points to features of the experience which is perceived as the most relevant and important. Through this function, metaphors clarify abstract ideas by tangible, visual and sensual images (Neisser, 2003).…”
Section: Introductionmentioning
confidence: 99%